DESIGN OF RIGID PAVEMENT THICKNESS (RIGID PAVEMENT) ROAD BENDANG - MUHAMMAD SAID SAMARINDA CITY - YANI, SUR (KURVA S JURNAL MAHASISWA, 2014)
Increased road pavement conditions that exist today many good damage caused by natural factors, as well as the human factor in this case the vehicle up to a need to increase in order to meet the needs of the higher traffic, in planning as a basis for execution to consider factors including comfort , security and other factors that support good planning and planned. At this time the level of service it is still lacking, so the need to build new roads or road improvements should be planned carefully in order to result in a plan that efisienserta environmentally friendly. The need the need for road infrastructure is an expected by society and is a supporting factor smoothness of the economy. Pavement Thickness planning Bendang-Muhammad Said Samarinda worked with Planning Calculation Method Cement Concrete Pavement (Pd-T-2003) and has the data that already exists planning rigid pavement is obtained plate thickness 27 Cm. For the type of reinforcement used by reinforcing continued reinforcement, obtained planning cement concrete pavement thickness and reinforcement in the form of Dowel and Tie Bar is able to support the load that crosses the road Bendang-Muhammad Said.